Peran Guru BK dalam Mendukung Perkembangan Emosional pada Anak Tunalaras (Ganguan Emosi dan Prilaku) - Giska Khoerunisa; Hunainah Hunainah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Emotional development is a crucial aspect in shaping children's personality and social abilities. Children with emotional and behavioral disorders, known as "tunalaras" children, often struggle to express their feelings appropriately and behave according to social norms, thus requiring support from the school environment, particularly through the role of Guidance and Counseling (BK) teachers. This study aims to explore in depth how BK teachers at SKH Bina Citra Anak support the emotional development of tunalaras children. The study uses a descriptive qualitative approach with in-depth interviews conducted with BK teachers as the primary informants. The findings reveal that BK teachers act as emotional companions who deal with various emotional characteristics of tunalaras children, such as impulsive, aggressive, and destructive behaviors. Teachers implement personal approaches to manage children's emotions, such as taking them to a quiet room, engaging in empathetic dialogue, and building safe relationships. Major challenges stem from the children’s social and environmental conditions, such as broken homes and external pressures. This research is expected to provide practical contributions to schools and related parties in creating a more empathetic and supportive educational environment for tunalaras children.